2017
DOI: 10.1089/met.2017.0008
|View full text |Cite
|
Sign up to set email alerts
|

Atherogenic Indices Are Increased in Elderly Patients with Unipolar Depression—Case–Control Analysis

Abstract: All three atherogenic indices were increased in elderly patients with depression. Since depression and age are associated with elevated risk of cardiovascular events, elderly patients with depression should be carefully monitored for abnormal lipid status to reduce their cardiovascular risk. The role of lipid abnormalities in the pathogenesis of depression requires further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Based on the present results, we have proposed lower serum HDL-C as a predictive blood biomarker of SOD especially for first-episode drug-naïve MDD patients. Supporting the present study, several studies have reported that serum HDL-C is negatively correlated with SOD in patients with MDD (Lucka et al, 2017;Shin et al, 2008). HDL-C is known to be carried by a lipoprotein, HDL (Camont et al, 2011).…”
Section: Discussionsupporting
confidence: 86%
“…Based on the present results, we have proposed lower serum HDL-C as a predictive blood biomarker of SOD especially for first-episode drug-naïve MDD patients. Supporting the present study, several studies have reported that serum HDL-C is negatively correlated with SOD in patients with MDD (Lucka et al, 2017;Shin et al, 2008). HDL-C is known to be carried by a lipoprotein, HDL (Camont et al, 2011).…”
Section: Discussionsupporting
confidence: 86%
“…33 Blood lipids consist of TC, TG, LDL, and HDL. 34 HDL is one of the serum lipids, and high serum HDL levels are associated with a decreased risk of vascular illnesses. Previous studies have indicated that depression is related to reduced HDL-C and increased TC or LDL-C and TG, but there are also some contrary data.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Blood lipids consist of TC, TG, LDL, and HDL . HDL is one of the serum lipids, and high serum HDL levels are associated with a decreased risk of vascular illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, there were changes in lipid parameters as low levels of: cholesterol (statistical insignificant), LDL-cholesterol (statistical insignificant) and HDL-cholesterol (p<0.05) in MD patients vs. control (Table 1). From the point of view of atherogenic indices, many researchers believe that they could play an important role in the evaluation of the depression risk [19][20][21]. Our study showed that AI and HeartScore values ( Moreover, for MD patients, the average value of HeartScore is over 2, which means an intermediate cardiovascular risk for them.…”
Section: Resultsmentioning
confidence: 50%
“…• Mild depression (10)(11)(12)(13)(14)(15)(16)(17)(18)(19) • Severe depression (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) All the patients received physical examination, laboratory tests and comprehensive psychological evaluations. We retrieved demographic information (age, sex, ethnicity and smoking) and clinical information (height, weight, body mass index, blood pressure, glucose serum levels and a lipid panel serum).…”
Section: For Depression Assessment It Has Been Used Geriatric Depressionmentioning
confidence: 99%